The Analysis of the Characters' Power Relations in Paulo Coelho’s Eleven Minutes - Imbron, Ahmad (English Literature Study Program, 2023)
This study aims to find power relations in the novel Eleven Minutes by Paulo Coelho. The researcher focuses on analyzing the forms of power relations between Maria and the male characters in the novel and her resistance against them. This study applies the power relations theory initiated by Michel Foucault. This type of research is classified as literary criticism with a sociological approach. Data collection in this study used documentation techniques by reading and highlighting sentences, dialogues, and quotations. Furthermore, analyzing the data is carried out by classifying, interpreting, analysing, and drawing conclusion. The result of this study indicates that Maria has power relations with the male characters in the novel. The male characters are the boyfriend and Malfson as the partners, the owner of a draper shop, Roger and Milan as the employers, the Arab man, Terence, and Ralf Hart as the clients. The forms of the power relations between Maria and the male character show that Maria has power over the male character by threatening and utilizing her beauty. Conversely, Mary is also often placed as a powerless party over the power exercised by men, such as being controlled and deceived. The resistance carried out by Maria was the resistance through discourse and disobedience. The resistance through the discourse was the summoning of a lawyer for an exploitative act committed by one of her employers. Meanwhile, the resistance through disobedience was carried out by refusing the pimp's orders by leaving from working as a prostitute in the Copacabana bar.